Work function tuned, surface Cs intercalated BiVO4 for enhanced photoelectrochemical water splitting reactions - Kalanur, Shankara S.; Seo, Hyungtak (Journal of Energy Chemistry, 2022)
Monoclinic BiVO4 is a widely researched semiconductor in solar water splitting owing to its suitable characteristics. However, BiVO4 faces limitations, such as the inefficient separation and transportation of photogenerated charges in the bulk and poor catalytic water oxidation reactions at the surface that affect the water-splitting efficiency. In this work, the Cs intercalation strategy at the surface of BiVO4 is proposed for the enhanced water splitting to H2 and O2 productions via the effective separation and transportation photogenerated charges and improved surface catalytic water oxidation reactions. The Cs ions are found to intercalate at the surface of BiVO4 and regulate the oxygen vacancies to provide active O2 production sites and stability. The surface intercalation of Cs boosts the photocurrent to 1.89 mA cm−2 at 1.23 V vs. reference hydrogen electrode (RHE). A stoichiometric evolution of H2 and O2 is recorded with a faradaic efficiency of 92%. The open-circuit voltage measurements confirmed the increase in the carrier lifetime with the work function tuning upon Cs intercalation. The proposed Cs intercalation strategy suggests an effective route to suppress the charge recombination with an increase in carrier lifetime and charge separation in BiVO4 for the enhanced PEC application.
Keywords: Annona structure; Monoclinics; Oxidation reactions; Photoelectrochemical water splitting; Photogenerated charge; Solar water splitting; Surface intercalation; Water oxidation; Water splitting reactions; Annona structure; BiVO4; Cesium; Photoelectrochemical water splitting; Surface intercalation